Global landscape, research hotspots, and evolutionary trends in childhood adversity and chronic disease research: a bibliometric analysis based on three databases - Yixia Zhou; Liuyin Jin; Weili Jiang; Lindan Sheng; Yang Li; Jianjiang Fang; Ying Wang (Frontiers in Public Health, 2026)
Background Adverse childhood experiences (ACEs) are increasingly recognized as important life-course determinants of chronic disease risk. However, the overall knowledge structure, research hotspots, and developmental trends in this field remain insufficiently characterized. This study aimed to systematically map the global research landscape of childhood adversity and chronic diseases through bibliometric analysis. Methods Literature related to childhood adversity and chronic diseases was retrieved from the Web of Science Core Collection (WoSCC), Scopus, and PubMed from database inception to December 31, 2025. After data conversion, merging, screening, and deduplication, bibliometric analyses were conducted to evaluate publication trends, contributions of countries, institutions, authors, and journals, collaboration networks, keyword co-occurrence, and citation impact using R, VOSviewer, and CiteSpace. Results A total of 5,369 publications were included. Annual publication output showed a sustained upward trend, especially after 2010, indicating rapidly growing scholarly interest in this field. The United States dominated in both publication output and citation impact and showed strong international collaboration, while the United Kingdom, Canada, Germany, and Australia were also major contributors. The University of California System and Harvard University were central in the institutional collaboration network. Keyword analysis identified major hotspots including childhood adversity/child abuse, depression, obesity, stress, risk factors, and cardiovascular disease, with emerging attention to chronic pain, chronic fatigue, and intergenerational effects. Highly cited studies were largely centered on the ACE framework and its associations with major adult health risks, reflecting a stable knowledge base for the field. Conclusions Research on childhood adversity and chronic diseases has developed into a mature and expanding interdisciplinary field with a clear international collaboration structure and an evolving thematic focus. The field is shifting from early association-based research toward mechanistic exploration and evidence integration. Future studies should strengthen the standardization of exposure and outcome definitions, expand longitudinal and causal evidence, and promote risk-stratified prevention and translational research.